System concept for small-scale biological methanation using electrolysis and trickle bed reactor - Larsson, Gustav (2021)
In the present study, the concept of a biological H2 methanation (BHM) system was created for four cases of scale which are determined by electrolyser scale. The system design is aimed to upgrade existing biogas to vehicle fuel quality, with a concentration of CH4 above 95% and H2S removal. The cases of scale and type of electrolyser are: 4.8 kW AEM electrolyser, 20 kW AEL electrolyser, 100 kWe AEL electrolyser and 550 kWe PEM electrolyser. Each case of scale can upgrade a biogas flow of 0.7, 2.4, 14.5 and 73.9 Nm3 respectively. A trickle bed reactor design at thermophilic conditions was chosen for the systems methanation process. A MATLAB model was created to simulate energy- and mass flows for the system. The simulation also includes economic parameters such as OPEX and CAPEX. Results of the simulation are presented as levelized cost of CH4 production (€/kWh) and specific CAPEX (€/kWe). Simulations of the system show a high upgrading performance with an output gas of above 95% CH4 with H2S removal. The system also increases CH4 yield of 60%. The system performs comparatively to traditional upgrading method. The economic results show that the system has an upgrading cost of 0.37 to 0.089 €/kWh and specific CAPEX of 3830 to 22 500 €/kW. The system cannot be considered economically competitive to traditional upgrading when no additional cost reductions are applied. The concept of upgrading by BHM also reduces carbon emissions from biogas production giving the system a good chance of receiving subsidies from greenhouse gas reduction initiatives. Larger scales of the system can then reach competitive upgrading costs by utilizing subsidies, electricity price reductions and heat recovery.